2020
DOI: 10.7705/biomedica.4759
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with multiple sclerosis and their caregivers in Colombia: One-year follow-up

Abstract: Introduction: Multiple sclerosis is a chronic inflammatory demyelinating disease associated with neurological disability. Clinical features include motor, cerebellar, visual, and sensory function alterations, as well as psychiatric comorbidities, such as depression, anxiety, and irritability. There is little literature available on the quality of life of patients and their caregivers.Objective: To assess the quality of life of patients with multiple sclerosis and their caregivers in Colombia given that there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
0
0
2
Order By: Relevance
“…The overall quality of life index in the study group averaged 65.39 points out of 100 (MusiQol) and is similar to the results obtained by Farran et al and Nickel et al 77 In contrast, Beltrán et al 78 reported a significantly higher score (84.1), and this difference may be since the participants in the Colombia study were characterized by good functional status (low EDDS scores) and short disease duration (average 4.8 years). In our study, the highest self-rated quality of life concerned RFa (81.37), RFr (69.83), and REJ (69.04) domains.…”
Section: Discussionsupporting
confidence: 87%
“…The overall quality of life index in the study group averaged 65.39 points out of 100 (MusiQol) and is similar to the results obtained by Farran et al and Nickel et al 77 In contrast, Beltrán et al 78 reported a significantly higher score (84.1), and this difference may be since the participants in the Colombia study were characterized by good functional status (low EDDS scores) and short disease duration (average 4.8 years). In our study, the highest self-rated quality of life concerned RFa (81.37), RFr (69.83), and REJ (69.04) domains.…”
Section: Discussionsupporting
confidence: 87%
“…Analysis of the study material showed that the QoL of the respondents was at an average level (50.73), which is consistent with the findings of Jamróz–Wisniewska et al [ 47 ]. However, other studies [ 65 , 66 , 67 , 68 , 69 ] indicate a significantly higher QoL among MS patients as measured by MusiQoL. In our study, the highest self–rated QoL concerned REJ (72.33), which is consistent with the findings of Beiske et al [ 69 ] and Nickel et al [ 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…De igual manera este ambiente positivo de aprendizaje propicia el bienestar emocional, a través del compartir conocimientos, experiencias en el cuidado, información actualizada, manejo de diversas problemáticas de salud comunes, mejorar la autoconfianza, disminuir la incertidumbre, el estrés 25 , y ayuda en el proceso de afrontamiento, disminución de la carga y finalmente a fortalecer su calidad de vida 26 , permitiéndoles a través de su reencuentro en el cuidado, proponer nuevos planes con elementos importantes para la práctica de los equipos interdisciplinarios en la atención de las personas con enfermedad crónica y sus familias 27 .…”
Section: Discussionunclassified